THE QURAN AND EFFECTIVE COMMUNICATION STRATEGIES FOR INTER-RELIGIOUS TOLERANCE - Muhammad Rizkon; Muhammad Azizan Fitriana; Samsul Ariyadi (PT. Jurnal Center Indonesia Publisher, 2025)
Diversity is an inevitability that cannot be avoided. It is a sunnatullah that should be done without consent. When diversity is combined with various assumptions of truth, an intolerant attitude arises. This problem is caused by a misunderstanding of the message of religious tolerance, which causes its adherents to appear with different faces. Therefore, the Qur'an explains what tolerance really is in Islamic teachings. Based on this problem, the researcher is interested in conducting a comparative analysis of how the interpretations of Hamka and Ali As-Ṣabūnī are related to religious tolerance, as well as the strengthening of the socio-historical background of both of them towards this interpretation. This study uses a qualitative approach with a comparative study method. Data collection consists of literature studies and observations. Descriptive analysis is used in the comparative analysis method. Lucien Goldmann's genetic structuralism theory is one of the theories used to strengthen research as a surgical tool. This theory explains that a work or text is the work of its own author, along with the historical reality that conditions the emergence of the work or text. To improve the analysis of this research, discussions of scholars and interpreters of the verses of the Qur'an related to religious tolerance are also used. Research shows that Hamka and Ali As-Ṣabūnī generally agree that coercion in embracing religion is not allowed. However, Hamka directs the meaning of religious tolerance with the applicable conditions and limitations. This study also refers to the theory of genetic structure which states that the tendency of general and specific interpretations of poems on religious tolerance cannot be separated from the socio-historical context of each community in which the two figures lived. This assumption is that the works of the two figures are not only personal works, but also the works of their respective communities and the social and historical realities of their respective times.